Alternativas para reflexionar aspectos críticos de la ciencia en el aula - Solbes-Matarredona, Jordi; Torres-Merchán, Nidia Yaneth (Revista Científica, 2015)
This paper is part of a research about the use of scientific-social issues to promote critical thinking skills in university students. The first part presents the considerations of a group of teacher training students about the criticality of science and what they understand about critical science. It also presents and discusses the experiences of some researchers who were persecuted because of their scientific contributions with social implications or scientific social issues.